Identificación y metodologías de sistemas para la delimitación de territorios (2010)
This document identifies the main issues affecting the delimitationof territories and explores the conceptual approachesfor describing the relationship of the territories understood asorganizations with their environment. Subsequently, we studiedthe systems methodologies known as soft systems methodology,SSM, and complex adaptive systems, CAS. Finally, the advantagesof systemic approaches to territorial delimitation are shown.